Activation of the STAT5 Signaling Pathway by Yiqi Jiedu Formula Induces Regulatory T Cell-Mediated Alleviation of Corneal Immunopathological Damage in Mice With Recurrent Herpes Simplex Keratitis - Xiao, Shuyu; Yang, Yang; Miao, Wanhong; Lyu, Chunming; Tao, Jinhua; Yu, Ying (Frontiers in Pharmacology, 2022)
This study aimed to investigate the effect of Yiqi Jiedu (YQJD) formula on the repair of corneal lesions in mice with recurrent herpes simplex virus keratitis (HSK). Sixty female BALB/c mice were randomly divided into three groups: a normal control group (Naive), a recurrence model group (Re), and a YQJD group. After inducing recurrence by ultraviolet irradiation, the ocular surfaces of different groups of mice were observed using a slit lamp and photographed, and ocular surface scores were calculated. The abundance of CD4+CD25+Foxp3+ regulatory T (Treg) cells was determined by flow cytometry in peripheral blood and spleen cells. The CD4+Foxp3+ Tregs were assessed by immunofluorescence in the cornea. The levels of the cytokines IL-10 and TGF-β in serum and splenocyte culture supernatants were detected by enzyme-linked immunosorbent assay. Furthermore, the activation status of the STAT5 signaling pathway was examined by protein blotting, and the effect of YQJD on Treg cells through inhibition of the STAT5 pathway was observed in vitro. YQJD alleviated corneal inflammation by enhancing the STAT5 signaling pathway, thereby promoting the differentiation of CD4+CD25+Foxp3+ Treg cells, increasing the levels of anti-inflammatory cytokines such as IL-10 and TGF-β, and maintaining immune tolerance. YQJD increased the proportion of CD4+Foxp3+ Treg cells; also, in the cornea, YQJD inhibited the aggregation of macrophages and CD4+ cells and reduced the proportion of Th17 cells and other pro-inflammatory cells. Moreover, YQJD promoted the secretion of IL-4 to protect the cornea, leading to the mitigation of corneal immunopathological damage. YQJD reduced corneal lesions in recurrent HSK mice by stimulating Treg cells, inducing immune tolerance, and inhibiting corneal immunopathological responses via modulation of the STAT5 signaling pathway.